The spinal nerves that constitute the plexus lumbosacrales of porcupines (Hystrix cristata) - Aydin, A.; Dinc, G.; Yilmaz, S. (Czech Academy Agricultural Sciences, 2009)
In this study, the spinal nerves that constitute the plexus lumbosacrales of porcupines (Hystrix cristata) were investigated. Four porcupines (two males and two females) were used in this work. Animals were appropriately dissected and the spinal nerves that constitute the plexus lumbosacrales were examined. It was found that the plexus lumbosacrales of the porcupines was formed by whole rami ventralis of L1, L2, L3, L4, S1 and a fine branch from T15 and S2. The rami ventralis of T15 and S2 were divided into two branches. The caudal branch of T15 and cranial branch of S2 contributed to the plexus lumbosacrales. At the last part of the plexus lumbosacrales, a thick branch was formed by contributions from the whole of L4 and S1, and a branch from each of L3 and S2. This root gives rise to the nerve branches which are disseminated to the posterior legs (caudal gluteal nerve, caudal cutaneous femoral nerve, ischiadic nerve). Thus, the origins of spinal nerves that constitute the plexus lumbosacrales of porcupine differ from rodantia and other mammals.
Keywords: lumbosacral plexus; nerves; posterior legs; porcupines (Hystrix cristata)